The Hattaiyah Method and Its Contribution to The Development of Qur'anic Recitation - Fathi Humaidy; M.Roihan Nasution; M.Nuh Siregar (Eduvest - Journal of Universal Studies, 2024)
Reading the Quran is a worship that is obligatory to all Muslims, But many Muslims today still cannot read the Qur'an. Therefore, many scholars made a breakthrough by creating an easy and fast method of reading the Qur'an. One of these methods is Hattaiyah which has been used by the Mawaridussalam Islamic Boarding School in helping students and their communities give hope to be able to read the Qur'an. This research is a type of qualitative research of a field nature (Fieled Reserch) the main source in this research as the main reference material is the book Hattaiyah Method and students. The results of this study show that the Hattaiyah method has a very large contribution in the development of the science of Qiroat of the Quran. Both in terms of education, parenting and social different communities.  Then this method also greatly contributes to parenting such as reducing the percentage of student violations, making it easier for students to use Arabic, and making students feel at home in pesantren. This study contribute to the community around the pesantren which is helped to overcome the problem of Qur'anic illiteracy in the area. The conclusion of this research is that Harrttaiyah's method has a very large contribution in eradicating the problem of Qur'anic illiteracy that currently occurs. This method is hoped that it will be a solution to make the muslim love the Qur'an by practicing it in order to create a life that is part of the world and the Hereafter.